Answer:
[tex]37^3 = 50653[/tex]
Step-by-step explanation:
Given
[tex](x - y)^3 = x^3 - 3x^2y + 3xy^2 - y^3[/tex]
Required
Find [tex]37^3[/tex]
Express 37 as 40 - 3
So, we have:
[tex]37^3 = (40 - 3)^3[/tex]
Compare to [tex](x -y)^3[/tex]
[tex]x = 40\ and\ y = 3[/tex]
Substitute 40 for x and 3 for y in [tex](x - y)^3 = x^3 - 3x^2y + 3xy^2 - y^3[/tex]
[tex](40 - 3)^3 = 40^3 - 3*40^2*3 + 3*40*3^2 - 3^3[/tex]
Evaluate all exponents
[tex](40 - 3)^3 = 64000 - 3*1600*3 + 3*40*9 - 27[/tex]
Evaluate all products
[tex](40 - 3)^3 = 64000 - 14400 + 1080 - 27[/tex]
[tex](40 - 3)^3 = 50653[/tex]
Hence:
[tex]37^3 = 50653[/tex]